A novel method to assess degree of crystallinity of aramid filament yarns. (July 2013) - Uppal, Rohit; Ramaswamy, Gita N; Loughin, Thomas
An equation was developed to predict the morphology of aramid fibers using dissolution time ( t ) data of Kevlar and Nomex multifilament yarns, which were heat set at various temperatures. The degree of crystallinity of the fibers was characterized by WAXS and the dissolution time of the samples was measured. The degree of crystallinity and dissolution time of the fibers increases with both heat treatment time and heat treatment temperature. The coefficient of correlation between1 / t and the X-ray degree of crystallinity was found to be −0.88 for Nomex aramid and −0.95 for Kevlar aramid multifilament yarns. The dissolution times of completely amorphous and fully crystalline fibers can be predicted using regression and were substituted in a novel equation to characterize the morphology of the aramid fibers. New equations were proposed to assess the degree of crystallinity of the aramid multifilament yarns. For Nomex, the equation is χ c = [(0.053) − (1 / t )]/(0.00054). For Kevlar, the equation is χ c = [(0.12) − (1 / t )]/(0.0015).